(3CSFdI GdbQBf GdeLjO hCLhHJgG ef ZQGFH Bj GdJfRjd (B:s 1236 (3SDGd hLhGH (B/s - (3GdQGRj, eMeO Hf CHj HcQ Hf YHO GdbGOQ,s (3J(B. (3HYO (B666 (3g`(B.s ((3HjQhJ (B:s (3GdecJHI GdYUQjI,s, 2005)
(3jJfGhd GdcJGH CSFdI Yf GdbQBf hELGHJgG(B.s
Keywords: (3GdbQBfs -- (3ZQjHs -- (3GNJHGQGJ, CSFdI, EdN(B.s